The anthropological lens : harsh light, soft focus - Peacock, James L. (Cambridge University Press, 2001)
"Anthropology is a complex, wide-ranging, and ever-changing field. This clear, coherent, and well crafted book is a revised version of a very successful text first published in 1986, designed to supplement standard textbooks and monographs. It covers the central concepts, distinctive methodologies and philosophical as well as practical issues of cultural anthropology, and it is accessible to the anthropological novice while being of value to the professional. The updated version covers current issues in cultural anthropology, and includes topics such as globalization, gender, post-modernism and public issues, and reflects changes in perspective and language."--Jacket